A model for the jitter of a ring oscillator under sinusoidal interference on the power supply. (May 2018) - Shi, Zhan; Luo, Lan; Lei, Menglei; Su, Tao
Abstract: This paper presents a model with analytical expressions for the jitter of a ring oscillator (RO) caused by single-tone sinusoidal interference on the power supply. The value of the jitter can be calculated given the static delay of the inverter and the size of the RO. The model explains the relationship between the jitter and the interference parameters, such as frequency and amplitude. Transistor-level simulations and test-board measurements are performed. The jitter calculated from the model corresponds well with the experimental results over a wide frequency range. The positions of the local maxima and minima in the frequency response are precisely calculated by the model. The jitter model is applicable even under large-amplitude interference. The unusual negative-growth behavior in the amplitude response predicted by the model is also observed in the experimental results. The traditional linear theory for the jitter of a ring oscillator is based on the assumption of a small signal. The model in this paper is valid for more general cases, as it can be used to explain and predict key features of jitter.